201Tl-labeled Prussian blue and Au@Prussian blue nanoprobes for SPEC-CT imaging: influence of the size, shape and coating on the biodistribution. Issue 10 (7th September 2017) - Maurin-Pasturel, Guillaume; Rascol, Estelle; Busson, Muriel; Sevestre, Samuel; Lai-Kee-Him, Joséphine; Bron, Patrick; Long, Jérôme; Chopineau, Joël; Devoisselle, Jean-Marie; Guari, Yannick; Larionova, Joulia
Abstract : 201 Tl-labeled Prussian blue and core@shell Au@Prussian blue nanoparticles coated with the phospholipidic bilayer and dextran were investigated in vivo as nanoprobes by usingSPECT-CT scintigraphy. Abstract : 201 Tl-labeled Prussian blue and Au core@Prussian blue shell nanoparticles were synthesised and investigated in vivo as nanoprobes by using SPECT-CT scintigraphy. We demonstrate that the size, morphology and nanoparticle coating affect the kinetics of the nanoparticle biodistribution.